GLASS CEILING: A STUDY ON THE FACTORS OF THIS PHENOMENON IN BRAZIL FROM THE PERCEPTION OF WOMEN MANAGERS - Carneiro, Luziberto Barroso; Gomes, Débora Gomes de; Cruz, Ana Paula Capuano da; Frare, Anderson Betti (SINERGIA - Revista do Instituto de Ciências Econômicas, Administrativas e Contábeis, 2022)
This study aimed to analyze how the factors that make up the glass ceiling phenomena impact the career of Brazilian women managers from their point of view, by a survey with women managers who have completed or attended postgraduate courses in the areas of management, controlling or finances. For Brazilian women managers, the factors that have impacted the most on glass ceiling are society’s culture, organizational structure and culture, management demographics, and discrimination. It is concluded that women have faced the glass ceiling mainly by their efforts and qualification, breaking successive barriers while still seeking to maintain a harmonious life. However, changes in the culture of society and companies are necessary to provide equity of gender.